Ultraviolet A-induced cathepsin K expression is mediated via MAPK/AP-1 pathway in human dermal fibroblasts. - Qingfang Xu (Public Library of Science (PLoS), 2014)
Background Cathepsin K (CatK), a cysteine protease with the potent elastolytic activity, plays a predominant role in intracellular elastin degradation in human dermal fibroblasts (HDFs), and contributes to solar elastosis. In previous studies, CatK expression was downregulated in photoaged skin and fibroblasts, but upregulated in acute UVA-irradiated skin and fibroblasts. The underlying mechanisms regulating UVA-induced CatK expression remain elusive. Objective This study investigates mechanisms involved in the regulation of UVA-induced CatK expression in HDFs. Methods Primary HDFs were exposed to UVA. Cell proliferation was analyzed using a colorimetric assay of relative cell number. Quantitative real-time RT-PCR and Western blot were performed to detect CatK expression in HDFs on three consecutive days after 10 J/cm2 UVA irradiation, or cells treated with increasing UVA doses. UVA-activated MAPK/AP-1 pathway was examined by Western blot. Effects of inhibition of MAPK pathway and knockdown of Jun and Fos on UVA-induced CatK expression were also measured by real-time RT-PCR and Western blot. Results UVA significantly increased CatK mRNA and protein expression in a dose-dependent manner. UVA-induced CatK expression occurred along with UVA-activated phosphorylation of JNK, p38 and Jun, UVA-increased expression of Fos. Inactivation of JNK and p38MAPK pathways both remarkably decreased UVA-induced CatK expression, which was suppressed more by inhibition of JNK pathway. Furthermore, knockdown of Jun and Fos significantly attenuated basal and UVA-induced CatK expression. Conclusion UVA is capable of increasing CatK expression in HDFs, most likely by activation of MAPK pathway and of AP-1, which has been shown to be the case for matrix metalloproteinases. As current strategies for selecting anti-photoaging agents focus on their ability to decrease MMPs' expression through inhibiting UV- activated MAPK pathway, future strategies should also consider their effect on CatK expression.